The Impact of Instagram Content Marketing and Brand 1mage on the Purchasing Choices of PT Anggie Rassly Andalan's Eyebrow Pencils - Anna Larasati; Fenny B.N.L. Tobing; Nenny Anggraini (Fundamental Management Journal, 2024)
Anna Larasati, The Impact of Instagram Content Marketing and Brand Image on the Purchasing Choices of PT Anggie Rassly Andalan's Eyebrow Pencils This research aims to analyze the impact of Instagram Content Marketing and Brand Image on the decision to purchase eyebrow pencils from PT Anggie Rassly Andalan. The primary data used is original data obtained through distributing questionnaires to 68 respondents using the purposive sampling method. The population in this study were all consumers who had purchased Anggie Rassly's eyebrow pencil twice. Samples were taken according to the Lemeshow formula because the population is unknown. The independent variables studied include ContentMarketing and BrandImage, while the dependent variable is purchasing decisions. The analysis carried out includes Validation tests, reliability assessments, tests of classical assumptions, t-tests, F-tests, multiple linear regression analyses, and the determination coefficient (R2). The results of this research show that: (1) There is an impact of content marketing on the decision to purchase Anggie Rassly's eyebrow pencil. (2) There is an impact of Brand Image on the decision to purchase Anggie Rassly's eyebrow pencil. (3) There is an influence of ContentMarketing and BrandImage together on the decision to purchase Anggie Rassly's eyebrow pencil.